Suicide in East German Literature : Fiction, Rhetoric, and the Self-Destruction of Literary Heritage. - Blankenship, Robert (Studies in German literature, linguistics, and culture., 2017)
This first book-length study of fictional suicides in East German literature provides insight into the complex and dynamic rhetoric of the GDR and the literariness of its literature.